EFFECT OF AN INTERVENTION PROGRAM IN THE DEVELOPMENT OF EMOTIONAL, MOTOR AND COGNITIVE SKILLS OF 5TH-6TH GRADERS - Anastasia Magkou; Eleni Zetou; Filippos Filippou; Nikolaos Vernadakis (Journal of Physical Education)
ABSTRACT The aim of this study was to investigate the effect of literature program on development emotional and motor skills of students aged 10-12 in the sport of volleyball. Students from 5th and 6th grade (Ν=257, 123 boys and 134 girls), participated in the research. The students were randomly divided into two groups. The first group (n=173) followed a 4 months literature program using the literary book "The Knight in Rusty Armor" and the second group (n=84) followed the typical Physical Education program. The teaching of emotional skills was combined with a program of learning the Volleyball cognitive backhand skill. Social-emotional intelligence was assessed with the questionnaire "Emotional Quotient-Inventory: Youth Version (EQ-I:YV)" by Bar-On and Parker, while the cognitive assessment of backhand service was carried out with criteria sheet 4 (p. 65) of the Physical Education book of the 5th-6th grade teacher. The non-parametric Friedman test - K related samples and the non-parametric Wilcoxon signed-rank test were used to evaluate the effect of the literature intervention. The results showed that the intervention program was effective with the students of the experimental group showing a significant improvement in terms of emotional skills: intrapersonal (P=0.290, Df(1), χ2: 1.119), empathy (P=0.128, Df(1), χ2: 2.312), social responsibility (P=0.610, Df(1), χ2: 0.261), adaptability (P=0.006, Df(1), χ2: 7.615), stress control (P=0.000, Df(1), χ2: 53.161) and general mood (P=0.790, Df(1), χ2:0.071). There was also an improvement in the cognitive of the back-hand service technique skill, (P=0.000, Df(2), χ2: 61.843). In contrast, students in the control group did not show any improvement in emotional skills and performance of cognitive backhand service skill. Therefore, the findings support the positive contribution of literature to the improvement of emotional and motor skills through the practice of the intervention program.